Toward a shared language for competency-based medical education. (3rd June 2017) - Englander, Robert; Frank, Jason R.; Carraccio, Carol; Sherbino, Jonathan; Ross, Shelley; Snell, Linda
Abstract: The paradigm shift brought about by the advent of competency-based medical education (CBME) can be characterized as an adaptive change. Currently, its development and implementation suffer from the lack of a lingua franca. A shared language is needed to support collaboration and dissemination across the world community of medical educators. The International CBME Collaborators held a second summit in 2013 to explore this and other contemporary CBME issues. We present the resulting International CBME Collaborator's glossary of CBME terms. Particular attention is given to the terms competency, entrustable professional activity ( EPA ), and milestone and their interrelationships. Medical education scholars and enthusiasts of the competency-based approach are encouraged to adopt these terms and definitions, although no doubt the vocabulary of CBME will continue to evolve.